1-octanol-water partitioning as a classifier of water soluble organic matters: Implication for solubility distribution. Issue 5 (4th May 2017) - Kuwata, Mikinori; Lee, Wen-Chien
ABSTRACT: Water-soluble organic matters (WSOMs) play an important role in determining magnitudes of climatic and environmental impacts of organic aerosol particles because of their contributions to hygroscopic growth and cloud formation. These processes are dependent on water solubility as well as distribution of this property in a particle, yet no method has been available to quantify such characteristics. In this study, we developed a theoretical framework to classify WSOM by 1-octanol-water partitioning that has a strong correlation with water solubility. 1-octanol-water partitioning coefficient also has a strong correlation with a traditional solid phase extraction method, facilitating interpretation of data from the technique. The theoretical analysis demonstrated that the distributions of WSOM classified by 1-octanol-water partitioning depend on (1) the volume ratio of 1-octanol and aqueous phases, and (2) extraction steps. The method was tested by using organic aerosol particles generated by smoldering of a mosquito coil, which serves as a surrogate for biomass burning particles. The WSOM extracted from the mosquito coil burning particles was classified by 1-octanol-water partitioning at different volume ratios. These solutions, including both the 1-octanol and aqueous phases, were nebulized to generate particles for measurements using an online aerosol mass spectrometer. The mass spectra indicated that highly oxygenated species tend to be highly soluble, while high molecular weight compounds are less soluble. Linear combinations of these mass spectra allowed the estimation of the mass fractions of WSOM partitioned to 1-octanol and aqueous phases, thereby facilitating the evaluation of the mass fractions of cloud condensation nuclei (CCN) active materials. © 2017 American Association for Aerosol Research